A Key to the Peshitta Gospels, Volume Two: Hē - Yōdh - Falla, Terry, (New Testament Tools, Studies and Documents ;, 2000)
This second volume of A Key to the Peshitta Gospels again provides a range of information, previously unpublished, essential to the study of the Peshitta Gospel text as a translation of the Greek and as a literary work in its own right. It is designed to serve both scholar and student. The Key , in which each word is classified according to its Syriac root, provides a) a Syriac-English dictionary, b) the notation of the part of speech for each Syriac term, c) referenced contextual phrases in English that illustrate a word's meanings, d) Syriac words of similar meaning, e) the corresponding Greek term for each Syriac term, f) a complete analytical concordance, g) an alphabetical index of Syriac catchwords, h) an index of Syriac verbal and nominal forms, i) an English index, j) an index of grammatical and general information. The Key can be used as a lexicon, concordance, thesaurus, critical guide to Syriac-Greek correspondences, or resource for the critical investigation of the Syriac text of the Peshitta Gospels..